A New Method for the Synthesis of Enantiomerically Pure Betti Base - Bian, Guangling; Yang, Shiwei; Huang, Huayin; Song, Ling (Synthesis, 2013)
We have developed a new method for the synthesis of enantiomerically pure Betti base. By using trifluoroacetic acid to replace the more traditionally used hydrochloride acid, the hydrolysis procedure used in the classical synthesis of racemic Betti base was carried out under milder conditions with an improved yield (up to 96%), which was followed by a new and efficient resolution with using recyclable (R)-1,1′-binaphthalene-2,2′-diyl sodium phosphate to provide enantiomerically pure (S)-Betti base in 95% yield with up to 99% ee and (R)-Betti base in 93% yield with 90% ee in one resolution step.
Keywords: Betti base; 1,1′-binaphthalene-2,2′-diyl sodium phosphate; chiral resolution; recycle; asymmetric synthesis